2017
DOI: 10.1111/chso.12222
|View full text |Cite
|
Sign up to set email alerts
|

Falling Out of Time: The Challenges of Synchrony for Children with Incarcerated Fathers

Abstract: Using a temporal lens, the article shows how fathers' incarceration leads to a loss of attunement to the temporal rhythms of their children's everyday lives. This lack of synchrony has implications for both the being and the becoming of the child. Through in-depth interviews, the article draws on data from a Danish study of mothers and children, aged 5-27, whose father/stepfather was incarcerated. Findings show the significance of a multifaceted understanding of time showing the implications of fathers' impris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…This finding is in line with longstanding observations, based on qualitative data, that rather than being characterized by 'closeness', conventional in-prison visitation situations can instead be stressful and intimidating (e.g. Arditti 2003; Austin and Hardyman 2004;Comfort 2008;Murray and Farrington 2008) or even perceived by visitors as a 'dead time' that is repetitive and devoid of meaningful events or interaction (Oldrup 2017). Such visitation experience can discourage some visitors from coming at all (Clark and Duwe 2017;Sturges 2002).…”
Section: Prison Visitingsupporting
confidence: 90%
“…This finding is in line with longstanding observations, based on qualitative data, that rather than being characterized by 'closeness', conventional in-prison visitation situations can instead be stressful and intimidating (e.g. Arditti 2003; Austin and Hardyman 2004;Comfort 2008;Murray and Farrington 2008) or even perceived by visitors as a 'dead time' that is repetitive and devoid of meaningful events or interaction (Oldrup 2017). Such visitation experience can discourage some visitors from coming at all (Clark and Duwe 2017;Sturges 2002).…”
Section: Prison Visitingsupporting
confidence: 90%
“…While family support is a crucial aspect of this, professionals also have an important role to play in supporting children affected by imprisonment in humane and non-stigmatising ways (Featherstone et al, 2014). Oldrup (2017) found that there are difficulties of synchrony between the child's world and the prison. The culture of 'us' and 'them' is damaging for the child or young person who must be reassured that services and professionals are there to work together to help them to develop and grow (Phillips and Gates, 2011).…”
Section: Supporting Children To Develop Positive and Appropriate Relamentioning
confidence: 99%
“…Changes in adolescents’ lives resulting from the absence of a father, who might have been a positive figure for some, could be the mechanisms through which paternal imprisonment may gradually work. Moreover, for many adolescents, not only may prison visits be emotionally stressful (Comfort, 2007), but the temporal rhythms of the prison may also interfere with their social life at home, because visiting and telephone times are fixed, which implies that the adolescent’s daily life also has to be organized accordingly (Oldrup, 2018). Other changes in the adolescent’s social life, such as spending more time with (deviant) friends and less time with family, will most likely also take effect more gradually after the imprisonment of a father.…”
Section: Discussionmentioning
confidence: 99%